Biological Tools to Study the Effects of Environmental Contaminants at the Feto-Maternal Interface - Chiara Mannelli; Francesca Ietta; Anna Maria Avanzati; Dariusz Skarzynski; Luana Paulesu (SAGE Publishing, 2015)
The identification of reproductive toxicants is a major scientific challenge for human health. Prenatal life is the most vulnerable and important time span of human development. For obvious ethical reasons, in vivo models cannot be used in human pregnancy, and animal models do not perfectly reflect human physiology. This review describes the in vitro test models representative of the human feto-maternal interface and the effects of environmental chemicals with estrogen-like activity, mainly bisphenol A and para-nonylphenol, with a particular emphasis on the effects at low, nontoxic doses similar to concentrations commonly detected in the population.